Distribution, economic injury level and sequential sampling of leaf folder (Cnaphaiocrosis medinalis) on rice (Oryza sativa) - CHANDER, SUBHASH; SINGH, VIDYA SAGAR (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the rainy season of 1997 and 1998 to study the spatial distribution of leaf folder(Cnaphalocrosis medinalis Guenee) on rice (Oryza sativa L.) in terms of its damage using Taylor's power law. The vahlesof aggregation parameter (b*) < 1.0 indicated regular distribution of the pest on the crop. Linear regression model for yield infestation relationship was found to be y = 91.8182-1.0434 X (R2 = 0.58) anyÂ  100.1869-0.5036 X (R2= 0.88) during 2 years. Based on gain threshold of 0.39 tonne/ha and regression coefficient of yield-infestation model, economicinjury level was determined as 4 % folded leaves during the first year and 8 % folded leaves during the second year atpanicle-emergence stage of the crop. Sequential sampling plan was formulated using distribution parameters, economicinjury level and error probability of 20 %.